Ultrafast creation of overlapping Rydberg electrons in an atomic BEC and Mott-insulator lattice - Mizoguchi, Manami; Zhang, Y.; Kunimi, M.; Tanaka, A.; Takeda, S.; Takei, N.; Bharti, V.; Koyasu, K.; Kishimoto, T.; Jaksch, D.; Glaetzle, A.; Kiffner, M.; et al. (Physical review letters, 2020)
We study an array of ultracold atoms in an optical lattice (Mott insulator) excited with a coherent ultrashort laser pulse to a state where single-electron wave functions spatially overlap. Beyond a threshold principal quantum number where Rydberg orbitals of neighboring lattice sites overlap with each other, the atoms efficiently undergo spontaneous Penning ionization resulting in a drastic change of ion-counting statistics, sharp increase of avalanche ionization, and the formation of an ultracold plasma. These observations signal the actual creation of electronic states with overlapping wave functions, which is further confirmed by a significant difference in ionization dynamics between a Bose-Einstein condensate and a Mott insulator. This system is a promising platform for simulating electronic many-body phenomena dominated by Coulomb interactions in the condensed phase.
Gesehen am 16.04.2021